PERINEURAL INJECTION THERAPY AS INTERVENTIONAL PAIN MANAGEMENT IN POST HERPETIC NEURALGIA : A CASE REPORT - Pringga, Gutama Arya; R, Rahmad; Pudji, Rosalyna; Kurniawan, Shahdevi Nandar; Suratmono, Mia Fajarningtyas (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Introduction: Post Herpetic Neuralgia is a neurological complication of herpes zoster resulting in neuropathic pain syndrome that worsens as a direct result of peripheral nerve damage that occurs during an attack of herpes zoster. It manifests as significant dermatomal pain or abnormal sensations and impacting various aspects of quality of life. Physically, patients may experience fatigue, anorexia, weight loss, insomnia, reduced mobility, and physical inactivity. Psychologically, it can lead to depression, anxiety, emotional burden, difficulty in concentration, and fear. Perineural Injection Therapy (PIT), developed by John Lyftogt, offers a treatment option for chronic neuropathic pain. Case Report: A 65-year-old male, currently unemployed for the past two years and previously worked as a tire repairman, came to the Husada Asih Clinic, with sharp, not radiating, and continuous left facial pain (VAS 9-10). He received treatment comprising Transcutaneous Electrical Nerve Stimulation (TENS) and Low Laser Light Therapy (LLLT) on the left face, combined with PIT injections using 5% dextrose at the left side of the face, targeting dermatomes left N V.1, V.2, V.3, and C3 , with repetition after three weeks. After the third injection, the pain at his left head was reduced (VAS 6). Pain at his left jaw and left neck reduced and became intermittently (VAS 5). Barthel Index : 20/20 (Independent). Discussion: The immediate clinical improvement in PIT administration is attributed to the sensorineural effects of dextrose. Clinically, pain decreases immediately or within 1-2 days after therapy. In this case, three series PIT resulted in significant pain relief, reduced burning sensation, improved left muscle motor function, full mouth opening, eased in eating and speaking, and the ability to resume social activities and work. Conclusion: Perineural injection therapy (PIT), previously developed by John Lyftogt, involves a series of subcutaneous injections using 5% dextrose in sterile water (D5W) near the affected nerve. This regenerative therapy offers pain control for PHN patients by targeting skin nerves as potential pain generators. PIT proves to be a valuable rehabilitation tool for managing PHN.